2007
DOI: 10.1080/00273170701710338
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Use of Growth Mixture Models in Psychological Research

Abstract: Psychologists are applying growth mixture models at an increasing rate. This article argues that most of these applications are unlikely to reproduce the underlying taxonic structure of the population. At a more fundamental level, in many cases there is probably no taxonic structure to be found. Latent growth classes then categorically approximate the true continuum of individual differences in change. This approximation, although in some cases potentially useful, can also be problematic. The utility of growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
261
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(268 citation statements)
references
References 69 publications
2
261
0
Order By: Relevance
“…Both methods perform the worst when there is within-class skewness in Z, but the 1-step approach is also likely to alter the number of classes needed to fit the data (consistent with the findings of Bauer, 2007).…”
Section: Number Of Classessupporting
confidence: 70%
See 1 more Smart Citation
“…Both methods perform the worst when there is within-class skewness in Z, but the 1-step approach is also likely to alter the number of classes needed to fit the data (consistent with the findings of Bauer, 2007).…”
Section: Number Of Classessupporting
confidence: 70%
“…As noted earlier, it is also possible that for the 1-step approach non-normality of Z may lead to an increase in the number of latent classes needed to fit the data (Bauer, 2007). This is a major concern in empirical studies because a change in the number of classes may alter their interpretation and hence bias their estimated effects on the distal outcome.…”
Section: Number Of Classesmentioning
confidence: 99%
“…Second, GMMs have been criticized; this method can result in the detection of trajectory classes that are not present in the data (Bauer 2007). One way of minimizing this risk is to not use GMM in an exploratory manner, but rather to specify specific a priori hypotheses based on prior research regarding the shape of the trajectories and the relationship between trajectory membership and covariates (Muthén 2004).…”
Section: Limitationsmentioning
confidence: 99%
“…Despite the growing popularity and increased usage (see e.g., Bauer, 2007), there are still certain limitations and concerns surrounding GMM that should be mentioned. Specifically, Bauer and Curran (2003) found that multiple latent classes could appear optimal when the population was only comprised of one group and when the data were nonnormal.…”
mentioning
confidence: 99%